The pleasure marriage : a novel - Ben Jelloun, Tahar, 1944- (Curbstone Books/Northwestern University Press, 2021)
"An epic romance that explores the intolerance for interracial marriage in Islamic Moroccan society. Amir enters a "pleasure marriage" with the Senegalese Nabou, disrupting the family and setting the stage for generations of tragedy"--